ASSESSING TARGETING ACCURACY OF THE VILLAGE FUND CASH TRANSFER PROGRAM: A POLICY EVALUATION PERSPECTIVE - Purnawati, Laily; Fauzia, Marliana Eka (JPAP: Jurnal Penelitian Administrasi Publik, 2026)
This study aims to evaluate the targeting accuracy of the Village Fund Direct Cash Assistance (BLT-DD) program in Sukowiyono Village, Karangrejo Subdistrict, Tulungagung Regency. Periodic evaluations are necessary as the community often questions the accuracy and transparency of the BLT-DD recipient selection process. Targeting accuracy is a crucial factor in ensuring the effectiveness of social policies in alleviating poverty and improving community welfare. The study employs a descriptive qualitative method with data collected through interviews, observations, and documentation. Informants were selected using a purposive sampling technique, based on their involvement and knowledge of the BLT-DD implementation. Data analysis was carried out using the interactive model of Miles and Huberman, with data validity tested through triangulation of sources and methods. The results indicate that the implementation of the BLT-DD program in Sukowiyono Village has generally run well, although it has not yet fully achieved accurate targeting. The effectiveness and efficiency are relatively high because the assistance meets basic community needs, and the data collection process is systematic, despite some delays in disbursement. The adequacy aspect remains low, as aid does not cover monthly household needs, while equity is suboptimal due to an uneven distribution. The village government demonstrates strong responsiveness through open complaint channels; however, accuracy issues persist, as some ineligible recipients are included and several poor residents remain unaccommodated.